2005
DOI: 10.1172/jci200522462
|View full text |Cite
|
Sign up to set email alerts
|

MyD88-dependent induction of allergic Th2 responses to intranasal antigen

Abstract: MyD88 is a common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
161
5
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(177 citation statements)
references
References 45 publications
7
161
5
4
Order By: Relevance
“…For example, asthma, which is characterized by a Th2-like environment (24), is exacerbated by low-dose LPS compared with high-dose LPS. Similarly, pDCs dampen lung inflammation into the lung of OVA-sensitized mice and in mice treated with cigarette extracts (10,42), proving their suppressive immune activity. In our experimental conditions we observed a similar path, as the ablation of pDCs in tumorbearing mice that were treated with low-dose LPS favored tumor arrest in contrast to mice treated with the high-dose LPS, implying a central role for pDCs in tumor progression in this model.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, asthma, which is characterized by a Th2-like environment (24), is exacerbated by low-dose LPS compared with high-dose LPS. Similarly, pDCs dampen lung inflammation into the lung of OVA-sensitized mice and in mice treated with cigarette extracts (10,42), proving their suppressive immune activity. In our experimental conditions we observed a similar path, as the ablation of pDCs in tumorbearing mice that were treated with low-dose LPS favored tumor arrest in contrast to mice treated with the high-dose LPS, implying a central role for pDCs in tumor progression in this model.…”
Section: Discussionmentioning
confidence: 92%
“…LPS elicits airway inflammation via the activation of TLR4 in a MyD88-dependent manner (10). However, the dose of LPS is of essential importance because low levels of LPS can induce a Th2-like immunity, whereas high levels of LPS induce Th1 responses in a mouse model of airway sensitization (11).…”
mentioning
confidence: 99%
“…An extensive literature examines the role of the MyD88 adaptor protein in Th1 vs. Th2 activation [26][27][28]. This led to a working consensus that MyD88-dependent signaling is preferentially required for Th1 responses, although it can also play a role in Th2 induction under some circumstances [29]. The MyD88-independent signaling pathways preferentially eliciting development of Th2-biased responses are not well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response is a highly regulated event involving a number of sophisticated and cross-regulated pathways shared by cellular players of the innate and acquired immune system (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). Whereas the TLRs are known to be underpinnings of the innate immune response, they are also intimately involved in events that direct the adaptive immune response (49)(50)(51).…”
Section: Tlrs and The Adaptor Molecule Myeloid Differentiation Factormentioning
confidence: 99%
“…Interestingly, the lack of IL-12 production via limited TLR activation during the inflammatory/immune response appears to lead to Th2 responses, suggesting that this type of response is a default pathway that occurs in the absence of IL-12. Investigations have demonstrated that MyD88 knockout mice were not able to generate a Th1 response when challenged with an infectious agent (57)(58)(59)(63)(64)(65)(66). Also, MyD88-mediated cytokines appear to provide a suppressive signal for a Th2-type response.…”
Section: Notch Ligands Regulate Cytokine-dependent Responses and Partmentioning
confidence: 99%